2003
DOI: 10.1515/znc-2003-7-814
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Cytotoxic Activity of Prenylated Bicyclic Acylphloroglucinol Derivatives from Hypericum amblycalyx

Abstract: Two new bicyclic acylphloroglucinol derivatives, hypercalyxone A (1-[5,7-dihydroxy-2-methyl-3-(3-methyl-but-2-enyl)-2-(4-methyl-pent-3-enyl)-chroman-8-yl]-2-methyl-propan-1-one, 1) and B (1-[5,7-dihydroxy-2-methyl-3-(3-methyl-but-2-enyl)-2-(4-methyl-pent-3-enyl)-chroman-8-yl]-2-methyl-butan-1-one, 2), have been isolated from the petroleum ether extract of the aerial parts of Hypericum amblycalyx, together with two further compounds (1-[5,7-dihydroxy-2-methyl-2-(4-methyl-pent-3-enyl)-chroman-8-yl]-2-methyl-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Phytochemical studies of St John's wort and other Hypericum species have resulted in the isolation of a wide range of natural products with anti-HIV, antiinflammatory, antitumor, antibacterial and antioxidant activities. These compounds include acylphloroglucinol derivatives, flavonoids and xanthones (Albert et al, 2002;Athanasas et al, 2004;Tanaka et al, 2005;Verotta, 2002;Winkelmann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies of St John's wort and other Hypericum species have resulted in the isolation of a wide range of natural products with anti-HIV, antiinflammatory, antitumor, antibacterial and antioxidant activities. These compounds include acylphloroglucinol derivatives, flavonoids and xanthones (Albert et al, 2002;Athanasas et al, 2004;Tanaka et al, 2005;Verotta, 2002;Winkelmann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Winkelmann et al . reported modest antistaphylococcal activity (32 µg/mL) for a related acylphloroglucinol lacking one of the additional isoprene units of 7 , further demonstrating the detrimental effects of the cyclization and/or increased lipophilicity (Winkelmann et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The results of these studies add to growing knowledge of the antimicrobial properties of acylphloroglucinol metabolites. Other studies have reported acylphloroglucinol derivatives possessing antimicrobial activity against staphylococci (Ishiguro et al ., ; Schempp et al ., ; Winkelmann et al ., , ; Gibbons et al ., ; Pecchio et al ., ; Henry et al ., ). A study by Socolsky et al .…”
Section: Resultsmentioning
confidence: 99%
“…The signal patterns and shift values of the remaining carbon and proton signals were similar to those of the bicyclic compound 1-[5,7-dihydroxy-2-methyl-2-(4-methylpent-3-enyl)chroman-8-yl]-2-methylpropan-1-one (7) previously isolated from H. amblycalyx. 12 The main difference between the two compounds was an additional C-3−C-4 double bond evident from the resonances of two methine carbons (δ C 123.2, C-3; 116.8, C-4) rather than two methylene carbons and of the corresponding protons H-3 (δ H 5.41, d, J = 10.0 Hz) and H-4 (δ H 6.59, d, J = 10.0 Hz). Compound 1 was determined to be 1-[5,7-dihydroxy-2-methyl-2-(4-methylpent-3-enyl)chromen-8-yl]-2-methylpropan-1-one and given the trivial name empetrikarinen A.…”
Section: ■ Results and Discussionmentioning
confidence: 99%